Local Cerebral Blood Flow Measured by CT After Stable Xenon Inhalation - Meyer, John Stirling; Hayman, L. Anne; Yamamoto, Masahiro; Sakai, Fumihiko; Nakajima, Shinji (American Journal of Neuroradiology, 1980)
A safe, practical, clinically applicable, noninvasive method for measuring local cerebral blood flow (LCBF) using inert xenon (Xes) and a 60 sec CT scanner has been developed in the baboon. Direct measurement of expired Xes concentration after short inhalation (4–7 min) of 40% Xes and the use of computer-programmed autoradiographic formulas allow accurate, reproducible measurements of LCBF using serial 60 sec scans of regions as small as 0.04 cm3. LCBF measurements are possible with a Single 1 min scan. The method reduces radiation exposure, obviates a costly fourth-generation scanner, avoids anesthetic effects of Xes, and reduces the 30 min/scan saturation period. It is less expensive than emission tomography and minimizes problems of overlap and Compton scatter inherent in 133Xe and positron-emission blood flow measurements. Regions of zero perfusion are demonstrable in three dimensions. Tissue solubility and partition coefficients, as well as LCBF, are measured in vivo with high resolution and reproducibility so that minor regional changes in physical properties of tissue that alter solubility are measured. These enhance the potential clinical usefulness of CT scanning.